Visionary Leadership Strategies: Navigating Uncertainty in the Workplace - Nugroho, Moch. Nur Syawalludin; Hartinah, Hartinah; Indira, Farah; Nadyatun, Fara; Yuliana A. (Journal of Quality Assurance in Islamic Education (JQAIE), 2025)
The era of disruption, characterized by uncertainty, complexity, and rapid technological change, demands adaptive, visionary leadership. This study aims to analyze visionary leadership strategies for addressing uncertainty in the modern workplace and to examine their role in building resilient, sustainability-oriented organizations. The research method is a qualitative approach using library research, examining various scientific sources such as journals, books, and academic articles published over the last 3 years. The results show that visionary leadership plays an important role in integrating long-term vision with adaptive actions that are responsive to environmental changes. Visionary leaders build a collaborative, innovative, and flexible organizational culture through effective communication and data-driven decision-making. The discussion also reveals that visionary leaders act as direction-setters, agents of change, spokespersons, and coaches, synergistically encouraging organizations to achieve resilience and competitive advantage.